Electoral Realignment and the Outlook for American Democracy. - Sabbatical Report - Paulson, Arthur C. (2006)
Keywords: dept.psc; faculty_collection; sabbatical_report

Employment in the Academe: The Impact of Public and Judicial Opposition to Affirmative Action. - Rai, Kul B. (2003)
Keywords: dept.psc; faculty_collection; sabbatical_report

The Impact of Public and Judicial Opposition to Affirmative Action. - Rai, Kul B. (2003)
Keywords: dept.psc; faculty_collection

Contra the New Deal: Roosevelt and His Critics 1933-1940. - Weed, Clyde (2003)
Keywords: dept.psc; faculty_collection; sabbatical_report

Globalization: People, Politics, and Places. - Critzer, John (2002)
Keywords: dept.psc; faculty_collection; sabbatical_report

Eager to Share?: Women Representatives in Britain, France and the United States. - Applewhite, Harriet (Academic year-2002; Political Science., 2001)
Keywords: dept.psc; faculty_collection; sabbatical_report

Does a Fourth Rus' Exist?: Concerning Cultural Identity in the Carpathian Region - Best, Paul J.; Stępień, Stanisław (Higganum, 2009)
Keywords: Europe, Eastern; Slavs; Slavs; United States; dept.psc; faculty_collection

The WTO Primer: Tracing Trade's Visible Hand Through Case Studies - Buterbaugh, Kevin; Fulton, Richard M. (Palgrave Macmillan, 2008)
Keywords: 20th century; 20th century; Commercial policy; History; History; General Agreement on Tariffs and Trade (Organization); History; International trade; World Trade Organization; dept.psc

Electoral Realignment and the Outlook for American Democracy - Paulson, Arthur C. (Northeastern series on democratization and political development, 2007)
Paulson's timely and authoritative study incorporates the latest data from the 2000 and 2004 elections into his analysis, and it offers vital perspectives on the outlook for the 2008 election.--(Source of description unspecified.)
Keywords: Election; Elections; Political parties; United States; United States; Presidents; dept.psc

The Lemkos of Poland: Articles and Essays - Best, Paul J.; Moklak, Jarosław (Carpatho-Slavic Studies Group and the Historia Iagellonica Press, 2000)
Keywords: Ethnic relations; History; Poland; Lemky; Poland; dept.psc; faculty_collection

The Aegean Sea After the Cold War: Security and Law of the Sea Issues - Chircop, Aldo E.; Gerolymatos, André; Iatrides, John O. (International political economy series, 2000)
Keywords: Aegean Sea Region; Security, International; Greece; Foreign relations; Greece; Law of the sea; Turkey; Turkey; dept.psc; faculty_collection

Realignment and Party Revival: Understanding American Electoral Politics at the Turn of the Twenty-First Century - Paulson, Arthur C. (Praeger, 2000)
Keywords: Election; Political parties; Presidents; United States; dept.psc; faculty_collection

Affirmative Action and the University Race, Ethnicity, and Gender in Higher Education Employment - Rai, Kul B.; Critzer, John W. (University of Nebraska Press, 2000)
Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and nonacademic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks, Asians, Hispanics, and Native Americans. The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non-elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities. Kul B. Rai is a professor of political science at Southern Connecticut State University. His works include "America in the Twenty-First Century: Challenges and Opportunities in Domestic Politics". John W. Critzer is a professor of political science at Southern Connecticut State University., "Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and non-academic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks Asian, Hispanics, and Native Americans." "The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities."--Jacket.
Keywords: Discrimination in higher education; Employment; United States; United States; Affirmative action programs; United States; Minority college administrators; United States; Minority college teachers; dept.psc; faculty_collection

The Pitch for Baseball: Washington's Plans for Nationals' Stadium - Wharton, Jonathan L. (Washington, DC's Challenges, 2005)
This is the fourth in a series of books dealing with Washington, DC. Like the first three, this also is the outgrowth of special seminars conducted in the Department of Political Science at Howard University. We examine Washington, DC's challenges, because it is vital to know the conditions under which the residents of the most powerful city in the world continue to live, based on sound empirical evidence.
Keywords: dept.psc

The WTO primer tracing trade’s visible hand through case studies - Buterbaugh, K.; Fulton, R. (The WTO Primer: Tracing Trade's Visible Hand Through Case Studies, 2007)
This book describes the WTO from its post-WWII beginnings in the General Agreement on Tariffs and Trade through a series of negotiated enhancements of these agreements. It describes the WTO's origins, structure, and growing pains as it has had to face challenges from within and without. © Kevin Buterbaugh, 2007. All rights reserved.
Keywords: dept.psc

Occupational segregation on the playing field: The case of major league baseball - Sack, AL; Singh, P; Thiel, R (Journal of Sport Management, 2005)
Occupational segregation by race and gender, though less common now than in the past, continues to be the norm rather than the exception in the sport industry. The purpose of this study was twofold. First, occupational segregation on the baseball playing field, often referred to as stacking, was discussed in light of human capital and social closure theories. Second, an attempt was made to replicate and extend a multivariate analysis of stacking by Margolis and Piliavin (1999) that challenges the dominant social science paradigm for explaining stacking. The present study uses more recent data than the Margolis and Piliavin study, as well as multinomial logistic regression analysis. The results reveal that stacking persists in Major League Baseball. They also reveal that the effect of race/ethnicity on assignments to playing positions is reduced when one controls for skills and physical characteristics such as speed and power hitting. The implications of this finding for sport management are examined.
Keywords: dept.psc

George F. Kennan and the birth of containment - The Greek test case - Iatrides, JO (World Policy Journal, 2005)
Keywords: dept.psc

Conclusion: The Aegean — Life-line and Battle-line - Chircop, Aldo; Gerolymatos, André; Iatrides, John O. (The Aegean Sea after the Cold War: Security and Law of the Sea Issues, 2000)
From the dawn of the Bronze Age and Homer’s immortal epics to the latest confrontation in the Middle East and the Persian Gulf, the Aegean Sea has been critically important to countless armies of merchants, warriors, and crusaders. As a geographic entity, it is a narrow body of water dotted with islands, islets, and rocks. However, the Aegean is both a link and barrier between the Mediterranean and Black Seas, and the maritime causeway between the land masses of Europe, Asia, the Near East, and Africa. In effect, this maritime highway has been one of history’s more productive crucibles for human accomplishment, as well as an arena of conflict and destruction.
Keywords: Geographic Entity; Greek Settlement; Narrow Body; Productive Crucible; Turkish Strait; dept.psc

Party change and the shifting dynamics in presidential nominations: the lessons of 2008 - Paulson, Arthur (Polity, 2009)
Presidential nominations in recent years have been settled with increasing speed, most of the time in the early stages of the primaries and caucuses, and certainly before the national convention, which has become more of a rally. Even when the battle for the Democratic Presidential nomination continued to the end of the primary season in 2008, it was settled before the convention. Analysts have emphasized the importance of the “invisible primary” and the front-loaded delegate selection schedule in explaining the early resolution of Presidential nomination contests. However, not enough attention has been paid to a much more fundamental change in our political parties and party system: The old umbrella parties have been replaced by ideological polarization between the parties and ideological homogenization within the parties. Our new party system dates back about forty years, and features increased ideological unity and decreased factionalism, making it easier to settle nominations. Even today's front-loaded nominating calendar would not have prevented some of the hotly contested conventions of the old umbrella parties. Polity (2009) 41, 312-330. doi:10.1057/pol.2009.4; published online 11 May 2009
Keywords: Elections; Nominations; Parties; Primaries; dept.psc

Late 19th century administrative reform in America: re-articulating Hamiltonian thought - O'Hara, Jonathan (International Review of Administrative Sciences, 2009)
In this article, the intellectual thought of a group of key late 19th century national administrative reformers is isolated and analyzed. These reformers were interested in reforming the civil, military and business administrative functions of the executive branch to provide for greater elite administrative supervision over and intervention in the national society and economy. The reformers often articulated their reform purposes, motives and goals in the Hamiltonian language of administrative authority and popular deference to executive administrative counsels. An important key to understanding this article is recognizing that while environmental social and economic conditions had changed significantly for the Gilded Age reformers since the American constitutional founding, many elements of the Hamiltonian tradition still resonated with the reformers a full century later. In this way, the historically transmitted ideology and rhetoric of Hamiltonian thought can be seen as having an independent, causative impact on the administrative reformers' purposes, motives and goals related to executive administrative reform.
Keywords: American founding; American progressivism; Developmental democracy; Gilded Age; Mugwumps; North America; United States; administrative reform; administrative system; bureaucracy; democracy; dept.psc; legal system; nineteenth century; planning process; political ideology

The post Cold war reestablishment of effective state authority in Latin America: can 'colombianization' tame Mexico's security crisis? - Olney, Patricia (Social Science Research Network, 2009)
This paper explores the Post Cold War origins of the organized criminal violence that once gripped Colombia and now grips Mexico and particularly the highly controversial counterinsurgency strategy used in Colombia that forms the basis for the current strategy in Mexico. It argues that ideology is a reason why the military aspect of these problems was neglected for so long and the reason its detractors see it as a strategy that reduces national sovereignty and endangers democracy when statistics on control of territory, reduction of violence and democratic progress demonstrate the opposite to be true. The paper uses the term “colombianization” to emphasize Colombia’s dramatic shift from almost ungovernable to one of the most stable countries in the region. Colombianization is defined not as a counterdrug strategy as are both the Colombian and Mexican U.S. assistance strategies but as an integrated, law-based, counterinsurgency strategy implemented from the bottom up that facilitates the establishment of elite consensus and puts the country on a path toward rule of law. Ironically, it was democratic and free market reforms that strengthened the forces of instability in both Colombia and Mexico and the militarization of security that appears to facilitate democratic stability. This study uses local level assessments of Plan Colombia and local interviews conducted in Chihuahua and Michoacán to evaluate the prospects of colombianization in urban and rural Mexico. Colombia's experience suggests that colombianization can stabilize the country and help reactivate the economy but democratic progress is painfully slow and the strategy has little impact on the drug industry and the corruption associated with it.
Keywords: Patricia Olney; SSRN; The Post Cold War Reestablishment of Effective State Authority in Latin America: Can 'Colombianization' Tame Mexico's Security Crisis?; dept.psc; ⛔ No DOI found

Trade and the Environment - Buterbaugh, Kevin (Encyclopedia of Violence, Peace, & Conflict (Second Edition), 2008)
This article examines the debate over the compatibility of trade and the environment. First, it discusses the range of arguments in the debate from trade being inherently beneficial to inherently harmful to the environment. Second, the entry examines the place of the environment within the GATT/WTO and various controversies surrounding the GATT/WTO and environmental protection. Finally, the article examines the role of multilateral environmental agreements in protecting the environment and their possible consequences for the international trading system.
Keywords: Eco-labeling; Environmental Kuznets curve; Environmental dumping; Environmental externality; Free-rider problem; GATT/WTO; Harmonization of standards; Multilateral environmental agreements; Precautionary principle; Race to the bottom; Sanitary and phytosanitary agreement; Technical barriers to trade agreement; Trade-environment debate; Trade–environment debate; dept.psc

Aristocratic and confederate republicanism in Hamiltonian thought and practice - O'Hara, Jonathan (Publius-the Journal of Federalism, 2008)
This article identifies and explores the presence of republican thought in the intellectual and policy writings of Alexander Hamilton, particularly as it applied to his theoretical understanding of the American executive branch. The article moves chronothematically, highlighting, through the Revolutionary, Constitutional, and Governmental periods of American political development, Hamilton's unique sense of republicanism with respect to international and domestic politics, as well as American political economy. The article not only attempts to demonstrate Hamilton's intellectual adherence to the republican tradition, but also his commitment to rhetorically applying the ideology to the realization of practical executive policy goals.
Keywords: dept.psc